Autophagy in the epithelial cells of murine seminal vesicle in vitro. Formation of large sheets of nascent isolation membranes, sequestration of the nucleus and inhibition by wortmannin and 3-ethyladenine - Kovács, A L; Réz, G; Pálfia, Z; Kovács, J (Cell and tissue research, 2000)
The spontaneous autophagic activity in epithelial cells of isolated tissue slices of murine seminal vesicle is strongly enhanced by short (5 min) pretreatment in a medium containing 0.03% Triton X-100. In addition to the significant increase in the cytoplasmic volume fraction and the mean size of autophagic vacuoles, the appearance of shorter or longer smooth membrane pairs located between cisterns of rough endoplasmic reticulum (RER) and in the vicinity of nucleus is also greatly stimulated. Their morphological features observed after application of various fixation methods, freeze-substitution and freeze-fracture techniques show that they are unclosed nascent isolation membranes, representing a unique class of intracellular membranes. They may grow around the nucleus, leading to its complete autophagic sequestration and degradation, which is observed here for the first time. Treatment with 3-methyladenine or wortmannin inhibits the formation of autophagosomes, leading to their regression with a halving time of 7 min. In contrast, these inhibitors cause extremely fast shrinking of nascent isolating membranes, leading to their complete disappearance within 7 min. We propose that the early events of autophagy involve three main steps: initiation, growth and closure, and suggest that the growth of nascent isolation membranes is reversible i.e. the membranes may be subject to disassembly before their closure is completed. Bending and closure of the isolation membrane and the stability of neighbouring cellular structures appear as important determinants of size regulation. These early steps of autophagy are good candidates for very fast accommodation to changing conditions and subtle regulation by phosphoinositide kinases as indicated by wortmannin sensitivity.